Opredelitev gozdnih območij s poudarjeno zaščitno funkcijo - Guček, Matjaž (Acta silvae et ligni, 2018)
We created determination procedure for forests with direct protection function according to the type of natural hazards and damage potential. The model was tested in two forest management units (Jezersko and Tržič) for two natural hazards % rockfall and avalanches. We determined areas with direct protection function on the basis of: 1) modelling risk areas of rockfall and avalanches, 2) data on buildings, settlements and infrastructure, and 3) area of forest. Numerous data were processed with different software, but mainly with MapInfo 10.5, ArcGIS 10.0 and Conefall - 3D friction model. We delineated direct protection function on the area of 625 ha, mainly due to protection against rockfall (44 %), avalanches (27 %), while 29 % of the area was determined due to rockfall and avalanches together. The degree of risk in the areas with direct protection function is mainly high (65 %). Our results showed that official data on areas with direct protection function were underestimated.
Keywords: avalanche; direct protection function; gozdovi; Karavanke; Karavanke Mts; modeling; modeliranje; naravne nevarnosti; natural hazards; neposredna zaščitna funkcija; padajoče kamenje; padajoče skale; plazovi; protection forest; rockfall; skalni podori; Slovenija; zaščitni gozdovi